ROS-Mediated Inhibition of S-nitrosoglutathione Reductase Contributes to the Activation of Anti-oxidative Mechanisms - Kovacs, Izabella; Holzmeister, Christian; Wirtz, Markus; Geerlof, Arie; Fröhlich, Thomas; Römling, Gaby; Kuruthukulangarakoola, Gitto T.; Linster, Eric; Hell, Rüdiger; Arnold, Georg J.; Durner, Jörg; Lindermayr, Christian (Frontiers in Plant Science, 2016)
Nitric oxide (NO) has emerged as a signaling molecule in plants being involved in diverse physiological processes like germination, root growth, stomata closing and response to biotic and abiotic stress. S-nitrosoglutathione (GSNO) as a biological NO donor has a very important function in NO signaling since it can transfer its NO moiety to other proteins (trans-nitrosylation). Such trans-nitrosylation reactions are equilibrium reactions and depend on GSNO level. The breakdown of GSNO and thus the level of S-nitrosylated proteins are regulated by GSNO-reductase (GSNOR). In this way, this enzyme controls S-nitrosothiol levels and regulates NO signaling. Here we report that Arabidopsis thaliana GSNOR activity is reversibly inhibited by H2O2in vitro and by paraquat-induced oxidative stress in vivo. Light scattering analyses of reduced and oxidized recombinant GSNOR demonstrated that GSNOR proteins form dimers under both reducing and oxidizing conditions. Moreover, mass spectrometric analyses revealed that H2O2-treatment increased the amount of oxidative modifications on Zn2+-coordinating Cys47 and Cys177. Inhibition of GSNOR results in enhanced levels of S-nitrosothiols followed by accumulation of glutathione. Moreover, transcript levels of redox-regulated genes and activities of glutathione-dependent enzymes are increased in gsnor-ko plants, which may contribute to the enhanced resistance against oxidative stress. In sum, our results demonstrate that reactive oxygen species (ROS)-dependent inhibition of GSNOR is playing an important role in activation of anti-oxidative mechanisms to damping oxidative damage and imply a direct crosstalk between ROS- and NO-signaling.